Evidence of male alliances in the Risso’s dolphin population of the northern Ionian Sea - Santacesaria, Francesca Cornelia; Cipriano, Giulia; Bellomo, Stefano; Clemente, Nicola; Fanizza, Carmelo; Lalinga, Simone; Maglietta, Rosalia; Pollazzon, Vittorio; Ricci, Pasquale; Carlucci, Roberto (Biologia Marina Mediterranea, 2025)
The study of cetacean social organization and the population dynamics provides valuable insights for developing effective conservation and management plans. This study analysed the strength of relationships among 61 photo-identified specimens (31 male and 20 female) sighted at least 10 times from July 2016 to September 2022, measuring the simple ratio association index (AI). The analysis revealed strong bonds (AI= 0.80-1.00) in 7.2% of dyads, with 79.3% being male-male, 13.4% female-male and 7.3% female-female associations. Four subgroups of males, organised in persistent and long-term associations were observed, revealing male alliances. Additionally, a strong bond between one subgroup of males and a potentially breeding female was reported, suggesting that male alliances could occur in a reproductive context. As the first analysis indicating the occurrence of male alliances, this study supports the hypothesis of a more complex and structured society in Risso’s dolphin population of the Northern Ionian Sea.